Rapid invasion of host cells by Toxoplasma requires secretion of the MIC2–M2AP adhesive protein complex - Huynh, My-Hang (Oxford University Press, 2003)
Vertebrate cells are highly susceptible to infection by obligate intracellular parasites such as Toxoplasma gondii, yet the mechanism by which these microbes breach the confines of their target cell is poorly understood. While it is thought that Toxoplasma actively invades by secreting adhesive proteins from internal organelles called micronemes, no genetic evidence is available to support this contention. Here, we report successful disruption of M2AP, a microneme protein tightly associated with an adhesive protein called MIC2. M2AP knockout parasites were >80% impaired in host cell entry. This invasion defect was likely due to defective expression of MIC2, which partially accumulated in the parasite endoplasmic reticulum and Golgi. M2AP knockout parasites were also unable to rapidly secrete MIC2, an event that normally accompanies parasite attachment to a target cell. These findings indicate a critical role for the MIC2–M2AP protein complex in parasite invasion.